Model Conceptual of Culture and Health-Seeking Behavior Among Mothers of Children with Stunting: A narrative review - Wiliyanarti, Pipit Festi; Choliq, Idham; Hasanah, Uswatun (South East Asia Nursing Research, 2024)
Socio-cultural factors can have a significant impact on the occurrence of stunting in children. Mothers with limited health literacy may need help comprehending the nuances of nutrition and malnutrition in children. This can lead to inadequate nutrition for their children, resulting in stunting. Unfortunately, a shortage of literature thoroughly explains the connection between health-seeking behavior theory and child stunting. This study entails a comprehensive narrative review that delves into the correlation between maternal health literacy, culture, and health-seeking behavior, particularly about child stunting. The CINAHL, PubMed, Scopus, Web of Science, and Cochrane Library databases were searched for published papers from 2009 to 2023. The search terms were maternal health literacy, culture, health-seeking behavior, and children with stunting or malnutrition. A comprehensive conceptual model can provide invaluable guidance for innovative research on caring for stunted children in rural areas. By amalgamating the concepts of culture and healing-seeking behavior with maternal health literacy, a more nuanced understanding of the problem of child stunting can be achieved. This can lead to the development of complementary and supportive interventions to improve maternal health literacy. Therefore, we should explore the potential benefits of such a model in our research endeavors.